Effect of a Ten-Month Moderate to Vigorous Physical Activity Program on VO2max and The Percentage of Body Fat in Overweight and Obese Children - Hall-López, Javier Arturo; Ochoa-Martínez, Paulina Yesica; Zamudio Bernal, Adrián; Sánchez León, Ricardo; Uriarte Garza, Luis Gerardo; Almagro, Bartolomé Jesús; Moncada-Jiménez, José; Sáenz-López Buñuel, Pedro (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2017)
Objective: Evaluate the effect of a moderate to vigorous physical activity program under the CATCH model on the body fat percentage and aerobic capacity in overweight or obese children. Method: Twenty-six children (15 males and 11 females) (age 9.4±0.3 years) diagnosed as overweight or obese from their body mass index (BMI) participated in a moderate to vigorous physical activity program under the CATCH model, 2 times a week for a 10-month period, comprised of moderate to vigorous exercises (56%) and evaluated using the System for Observing Fitness Instruction Time (SOFIT).  The body fat percentage was evaluated before and after the program using the equation by Slaughter et al., 1988 taking the anthropometrics measurements of triceps and media calf skin folds. The aerobic capacity (maximum oxygen uptake-VO2max) was determined through the 20-meter Multi-Stage Fitness Test using the equation proposed by Léguer et al., 1984. Results: The results showed a significant decrease in the body fat percentage (Δ% = -2.4, p = 0.022) and a significant increase in VO2max (Δ% = 11.3, p ≤ 0.001). Conclusion: Having moderate to vigorous physical activity under the CATCH model improved aerobic capacity and reduced the body fat percentage in overweight or obese children.